Nanomolar LL-37 induces permeability of a biomimetic mitochondrial membrane. Issue 47 (22nd November 2022) - Jiang, Xin; Yang, Chenguang; Qiu, Jie; Ma, Dongfei; Xu, Cheng; Hu, Shuxin; Han, Weijing; Yuan, Bing; Lu, Ying
Abstract : Single-molecule observations show that nanomolar LL-37 can directly permeate the lipid membrane in a lipid-specific and protein-independent manner. Abstract : LL-37, the only human host cathelicidin peptide, is proposed to be able to induce host cell apoptosis through mitochondrial membrane permeabilization (MMP). Detailed pathways of the LL-37-triggered MMP are however still disputed. It is generally believed that cationic peptides permeate a membrane mostly in conditions of micromolar peptide concentrations and negatively charged membranes, which are not usually satisfied in the mitochondrial circumstance. Herein, using a variety of single-molecule techniques, we show that nanomolar LL-37 specifically induces permeability of a phosphoethanolamine (PE)-rich biomimetic mitochondrial membrane in a protein-independent manner. The insertion dynamics of single LL-37 molecules exhibit different metastable states in bilayers composed of different lipids. Moreover, the PE lipids significantly facilitate adsorption and accumulation of LL-37 on the PE-rich bilayer, and produce deeper insertion of peptide oligomers, especially tetramers, into the bilayer. This work offers an alternative pathway of the LL-37-triggered MMP and apoptosis.